Robotic Surgery and Deep Infiltrating Endometriosis Treatment: The State of Art - Carlo Alboni; Ludovica Camacho Mattos; Antonio La Marca; Diego Raimondo; Paolo Casadio; Renato Seracchioli; Giorgia Gaia (IMR Press, 2023)
Objective: Surgical treatment of endometriosis, when indicated, has demonstrated to be effective in reducing painful symptoms and improve quality of life of patients affected with endometriosis. The minimally invasive approach via laparoscopy is the preferred method when compared with laparotomy but in the last two decades another minimally invasive approach has become available, the robotically assisted laparoscopic surgery. Robotic technology is widely used in different surgical branches, such as general surgery and urology. Moreover, the use of robotic surgery is already accepted for different gynecological procedures either for benign and for oncological diseases. The advantages of robotic surgery such as improve dexterity of movements, avoided tremor, increased magnification of 3-dimensional vision seem strategic in the context of a complex surgery as is deep endometriosis eradication. However, to date there is no unanimous consensus on whether robotically assisted procedures are a valid and safe alternative to laparoscopy in the treatment of endometriosis. Mechanism: In this narrative review we analyze the available literature assessesing the robotic treatment of all types of endometriosis and specifically deep infiltrating endometriosis, compared to the outcomes of conventional laparoscopy. Findings in Brief: Indeed, the evidence of safety and effectiveness of robotically assisted laparoscopy in endometriosis treatment is strong and almost unanimous. There is no clear superiority of one approach to the other but robotic-related advantages and future prospective are promising to be able to improve operative outcomes, reduce surgeon's fatigue and provide a technology easy to implement with a fast learning curve. Conclusions: Robotic technology applied to laparoscopy in the treatment of endometriosis could be seen as an effective and safe alternative to the conventional laparoscopic treatment.